Środowiskowe aspekty procesów poszukiwania i wydobycia gazu ze złóż niekonwencjonalnych typu shale gas - Monika Wójcik (Studia Ecologiae et Bioethicae)
Shale gas exploration and extraction processes create a potential threat for all environmental elements like air and noise emissions, contamination of surface and groundwater, soil pollutions, production of different types of waste, or increasing water consumption. The degree of potential environmental impact depends especially on location and size of a drilling rig, level of urbanization of an area, sensitivity of environment to pollution, and type of technological operations which depends on shale formation. The paper presents the main environmental hazards during shale gas exploration and extraction processes and ways of its reduction. Explain how investors can resolve problems with flowback water qualification, prepare drilling rig area or store hazardous materials and chemicals. Generally, the impacts of drilling processes on the environment are well recognized. Legal compliance with environmental legislation and procedures like Health Safety & Environment Management System or Environmental Management Systems can minimalize potential damages.